Multifaceted Effects of Intermittent Fasting on the Treatment and Prevention of Diabetes, Cancer, Obesity or Other Chronic Diseases - Tagde, Priti; Tagde, Sandeep; Bhattacharya, Tanima; Tagde, Pooja; Akter, Rokeya; Rahman, Md. H. (Current Diabetes Reviews, 2022)
Background: Obesity and diabetes are global epidemics resulting in a range of comorbidities. Both have been linked to an increased risk of hormonal imbalance, cancer, and other significant disorders, which are a concerning trend for cancer rates in the backdrop of rising obesity and diabetes rates worldwide. Around 1 in 10 persons in the United States and Canada have serious illnesses correlated to type 2 diabetes and early death. It is believed that the US economy alone spends 245 billion annually due to this health burden. Lifestyle modification with intermittent fasting protocol and proper diet helps lower blood glucose level, maintain the body mass index, and reduce inflammation, which is the main cause of all chronic diseases. Methods: We searched case series and clinical trials on type 2 diabetes, insulin resistance, cancer, thyroid, cardiovascular disease, or other inflammatory diseases in response to intermittent fasting in the PubMed, MEDLINE, and Google Scholar databases. Objective: In this review, we have focused on intermittent fasting-based approaches that are becoming more widely accepted for improving health and reducing unwanted effects in patients with type 2 diabetes, cancer, cardiovascular disease, neurodegenerative disease, obesity, thyroid, and hormonal imbalance; it is also contemplated whether intermittent fasting can be considered as a non-medicinal therapeutic option for persons suffering from chronic diseases. Conclusion: Intermittent fasting successfully reversed diabetes, thyroid, and high blood pressure, elevated lipid levels, and maintained the body mass index; also, studies have shown that it has been instructed to be followed for the treatment and prevention of cancer and neurodegenerative diseases.
Keywords: intermittent fasting